Monitoring knowledge translation and the impact of HI in European countries. (30th September 2020) - Delnord, M; Abboud, L A; Van Oyen, H
Abstract: Background: National health information systems (NHIS) report on the health of populations, the determinants of health and service use within countries. Thus far, the evaluation of HIS has largely focused on data production, and less on their impact in policy and practice. This entails that there is no standardized framework for monitoring the uptake of Health Information (HI) in the healthcare system. Methods: An international Delphi with public health professionals and policy makers allowed reaching agreement on criteria for monitoring the impact of NHIS, based on four domains: (a) Health information Evidence Quality, (b) HIS Responsiveness, (c) Stakeholder Engagement, and (d) Knowledge Integration. Next, we pretested the Index among participating countries in the European Joint Action on Health Information. Results: Over 130 public health professionals and policy-makers from 38 countries participated in the Delphi. The panel reached agreement on 30 criteria to monitor the impact of HIS in policy and practice; these constitute the HI-Impact Index. Eight countries participated in pretesting the HI-Impact Index. InfAct country representative found the HIS evaluation tool user friendly and the time needed to fill the evaluation acceptable. They noted however the need to refine the auditing guidelines further as to who shall be responsible for conducting the evaluation (i.e. multistakeholder evaluation vs. single governing body), and which type of population health data sources should be included as part of the evaluation. Conclusions: Knowledge translation facilitates the implementation of practices that will benefit population health and well-being. The HI-Impact Index addresses a growing demand for more transparency and accountability in the use of HI and scientific evidence within countries. Next steps consist in further piloting the HI-Impact Index for use in specific health areas (i.e. maternal and child health, cancer, antimicrobial resistance).